Asymmetric Dopaminergic Degeneration and Attentional Resources in Parkinson’s Disease - Ortelli, Paola; Ferrazzoli, Davide; Zarucchi, Marianna; Maestri, Roberto; Frazzitta, Giuseppe (Frontiers in Neuroscience, 2018)
Background: Attention is crucial to voluntary perform actions in Parkinson’s disease (PD), allowing patients to bypass the impaired habitual motor control. The asymmetrical degeneration of the dopaminergic system could affect the attentional functions. Objective: To investigate the relationship between the asymmetric dopaminergic degeneration and the attentional resources in Parkinsonian patients with right-side (RPD) and left-side (LPD) motor symptoms predominance. Methods: 50 RPD, 50 LPD and 34 healthy controls underwent visual (V), auditory (A) and multiple choices (MC) reaction time (RTs) tasks. For PD patients, these tasks were performed before and after a 4-week intensive, motor-cognitive rehabilitation treatment (MIRT). The effectiveness of treatment was evaluated assessing Unified Parkinson’s disease Rating Scale (UPDRS) III and Timed-up and Go Test (TUG). Results: RTs did not differ between PD patients and healthy controls. Before MIRT, no differences between LPD and RPD patients were observed in RTs (p=0.20), UPDRS III (p=0,60) and TUG (p=0,38). No differences in dopaminergic medication were found between groups (p=0.44 and p=0.66 before and after MIRT, respectively). After MIRT, LPD patients showed a significant reduction in MC RTs (p=0.05), V RTs (p=0.02) and MC-V RTs. A significant association between changes in RTs and improvements in UPDRS III and TUG was observed in LPD patients. Conclusions: attention does not differ among RPD patients, LPD patients and healthy controls. Only LPD patients improved their performances on attentional tasks after MIRT. We argue that the increased early susceptibility of the left nigrostriatal system to degeneration affects differently the cognitive modifiability and the neuroplastic potential. Our results could provide insight into new therapeutic approaches, highlighting the importance to design different treatments for RPD patients and LPD patients.